Insomnia Patients With Objective Short Sleep Duration Have a Blunted Response to Cognitive Behavioral Therapy for Insomnia - Bathgate, Christina J. (Sleep, 2016)
STUDY OBJECTIVES: This study examined whether individuals with insomnia and objective short sleep duration <6 h, a subgroup with greater risks of adverse health outcomes, differ in their response to cognitive–behavioral therapy for insomnia (CBT-I) when compared to individuals with insomnia and normal sleep duration ≥6 h. METHODS: Secondary analyses of a randomized, clinical trial with 60 adult participants (n = 31 women) from a single academic medical center. Outpatient treatment lasted 8 weeks, with a final follow-up conducted at 6 months. Mixed-effects models controlling for age, sex, CBT-I treatment group assignment, and treatment provider examined sleep parameters gathered via actigraphy, sleep diaries, and an Insomnia Symptom Questionnaire (ISQ) across the treatment and follow-up period. RESULTS: Six months post-CBT-I treatment, individuals with insomnia and normal sleep duration ≥6 h fared significantly better on clinical improvement milestones than did those with insomnia and short sleep duration <6 h. Specifically, individuals with insomnia and normal sleep duration had significantly higher insomnia remission (ISQ < 36.5; χ(2)[1, N = 60] = 44.72, p < .0001), more normative sleep efficiency (SE) on actigraphy (SE > 80%; χ(2)[1, N = 60] = 21, p < .0001), normal levels of middle of the night wake after sleep onset (MWASO) <31 minutes (χ(2)[1, N = 60] = 37.85, p < .0001), and a >50% decline in MWASO (χ(2)[1, N = 60] = 60, p < .0001) compared to individuals with insomnia and short sleep duration. Additionally, those with insomnia and normal sleep duration had more success decreasing their total wake time (TWT) at the 6-month follow-up compared to those with insomnia and short sleep duration (χ(2)[2, N = 60] = 44.1, p < .0001). Receiver–operating characteristic curve analysis found that using a 6-h cutoff with actigraphy provided a 95.7% sensitivity and 91.9% specificity for determining insomnia remission, with the area under the curve = 0.986. CONCLUSIONS: Findings suggest that individuals with insomnia and objective short sleep duration <6 h are significantly less responsive to CBT-I than those with insomnia and normal sleep duration ≥6 h. Using an actigraphy TST cutoff of 6 hours to classify sleep duration groups was highly accurate and provided good discriminant value for determining insomnia remission.